Using Grammarly to Enhance Students’ Academic Writing Skills - N. A. Zinkevich; T. V. Ledeneva (Дискурс профессиональной коммуникации, 2021)
The paper aims to present the results of the experiment in applying the online writing assistant Grammarly.com to evaluate ESP students’ essay writing skills. One hundred master students’ papers were processed by the application to identify persisting errors at a master’s level. Quantitative and qualitative methods enabled the researchers to analyze the essays by setting five parameters: audience, formality, domain, tone, and intent. At the other end, the application broke down the outcome by five measurable factors: correctness, clarity, delivery, engagement, and style issues. The representative number of the essays fed into Grammarly.com provided a vivid and reliable picture of which lexis, grammar, structure, or style issues still need addressing. The most common mistakes detected by Grammarly.com were punctuation, wordy sentences, redundancy, and the abundance of personal pronouns in a formal style. They show that the gaps in students’ academic writing need a remedial course. Another objective of the research was to explore the potential of the online writing tool for students’ self-study. Grammarly.com cannot do work for students: it cannot think for them, neither can it write for them, but it can help learners identify the reoccurring writing problems, eliminate them, and monitor the progress. The application could be particularly useful for advanced students. The functionality of the Grammarly premium version allows for a choice of styles, type of addressee, tone of writing, and many other nuances, which could be beneficial not only for studies but in future professional life. Nonetheless, despite Grammarly’s advanced features, it only suggests a better variant, sometimes it errs, and in no way is it a substitute for a teacher.